Analisis Pengaruh Nilai Konsumsi terhadap Niat Beli Pada Produk Sayuran Organik di Kabupaten Karawang - Mandasari, Rosdiana; Azzahra, Fatimah; Wicaksana, Indrajit (Jurnal Agrimanex: Agribusiness, Rural Management, and Development Extension, 2024)
The rise of the healthy lifestyle trend has increased public awareness and habits and started to switch to consuming organic agricultural products. One type of organic agricultural product is organic vegetables. This encourages changes in consumer perceptions and behavior. The purpose of this study was to analyze and identify the effect of consumption value on purchase intention on organic vegetables in Karawang. The population of this study were consumers who knew organic vegetables and had consumed organic vegetables in Karawang. This study took a sample of 115 respondents by purposive sampling. Data analysis using SEM-PLS analysis. The findings in this study are that consumption value has a positive and significant effect on purchase intention on organic vegetables in Karawang. Based on the results, there are three consumption values that have a greater influence, namely functional value, social value, and conditional value.